Análisis de los impactos socioculturales causados por la actividad turistica deportiva “regatas” en Vinces - Moran Cedeño, Karen Maoly (2021)
Without a doubt, tourism has evolved over the years but its purpose has not been affected because it still manages to awaken people's curiosity to know new places, have new experiences, reactivate the economy and above all it helps to disconnect for a moment of reality that is lived daily. On the other hand, adventure tourism has become an excellent option to enhance a tourist attraction, as long as it is suitable for its execution. Vinces has undoubtedly become a fundamental resource for the practice of adventure sports, a clear example of the aforementioned, are his famous regattas. This tourist activity has attracted a lot of attention from tourists due to its way of carrying it out and the adrenaline it provokes when doing it. The methodology used in this work is of a qualitative approach, the same one that will bring us relevance to the problem posed and facilitated its analysis and interpretation, thanks to the results obtained we were able to determine the impacts caused around tourism, likewise we determined that the regattas are the most relevant event within the Vinces canton, although as a result of these there are changes in habits and behaviors within the inhabitants.